Human embryonic stem cell-derived endothelial cell product injection attenuates cardiac remodeling in myocardial infarction - Spiroski, Ana-Mishel; McCracken, Ian R.; Thomson, Adrian; Magalhaes-Pinto, Marlene; Lalwani, Mukesh K.; Newton, Kathryn J.; Miller, Eileen; Bénézech, Cecile; Hadoke, Patrick; Brittan, Mairi; Mountford, Joanne C.; Beqqali, Abdelaziz; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Mechanisms contributing to tissue remodeling of the infarcted heart following cell-based therapy remain elusive. While cell-based interventions have the potential to influence the cardiac healing process, there is little direct evidence of preservation of functional myocardium. Aim The aim of the study was to investigate tissue remodeling in the infarcted heart following human embryonic stem cell-derived endothelial cell product (hESC-ECP) therapy. Materials and methods Following coronary artery ligation (CAL) to induce cardiac ischemia, we investigated infarct size at 1 day post-injection in media-injected controls (CALM, n = 11), hESC-ECP-injected mice (CALC, n = 10), and dead hESC-ECP-injected mice (CALD, n = 6); echocardiography-based functional outcomes 14 days post-injection in experimental (CALM, n = 13; CALC, n = 17) and SHAM surgical mice (n = 4); and mature infarct size (CALM and CALC, both n = 6). We investigated ligand–receptor interactions (LRIs) in hESC-ECP cell populations, incorporating a publicly available C57BL/6J mouse cardiomyocyte-free scRNAseq dataset with naive, 1 day, and 3 days post-CAL hearts. Results Human embryonic stem cell-derived endothelial cell product injection reduces the infarct area (CALM: 54.5 ± 5.0%, CALC: 21.3 ± 4.9%), and end-diastolic (CALM: 87.8 ± 8.9 uL, CALC: 63.3 ± 2.7 uL) and end-systolic ventricular volume (CALM: 56.4 ± 9.3 uL, CALC: 33.7 ± 2.6 uL). LRI analyses indicate an alternative immunomodulatory effect mediated via viable hESC-ECP-resident signaling. Conclusion Delivery of the live hESC-ECP following CAL modulates the wound healing response during acute pathological remodeling, reducing infarct area, and preserving functional myocardium in this relatively acute model. Potential intrinsic myocardial cellular/hESC-ECP interactions indicate that discreet immunomodulation could provide novel therapeutic avenues to improve cardiac outcomes following myocardial infarction.